Sensory Ganglionopathy and the Blink Reflex: Electrophysiological Features. (22nd January 2016) - Alam, Taimour; Barker, Alexander StJ.E.; Alix, James J.P.; Hadjivassiliou, Marios; Rao, Dasappaiah G.
Abstract: Background: Sensory ganglionopathy (SG) is characterised by asymmetrical sensory fibre degeneration, with the primary pathology occurring at the level of the dorsal root ganglion. It is seen in the context of autoimmune, paraneoplastic, and degenerative disorders. There is limited literature examining the electrophysiological correlate of the trigeminal ganglion and associated pathways, the blink reflex (BR), in cases of SG. Previous work has suggested that the BR is preserved in cases of SG associated with paraneoplasia. Methods: The local clinical neurophysiology database was searched for patients diagnosed with SG from peripheral nerve conduction studies in whom the BR was performed. Twenty-six patients were included in the final analysis. Results: Sjögren's syndrome constituted the most common SG aetiology (8/26), followed by idiopathic cases (7/26) and paraneoplasia (5/26). BR abnormalities were seen in 9 of the 26 patients (34.6%) across all aetiologies. No patients reported sensory disturbance in the distribution of the trigeminal nerve, indicating that the changes noted are subclinical. Three patients showed abnormality of the R1 response; in the remaining six patients, only R2 responses were affected. Conclusions: Subclinical abnormalities of both R1 and R2 can be seen in the context of SG of varying aetiologies, including paraneoplasia. Performing the BR in patients with suspected of having SG may be helpful in providing additional evidence of patchy sensory fibre involvement that is characteristic of the disease. RÉSUMÉ: Gangliopathie sensitive et réflexe de clignement : caractéristiques électrophysiologiques. Contexte: La gangliopathie sensitive (GS) est caractérisée par une dégénérescence asymétrique des fibres sensitives, la pathologie primaire étant localisée au niveau du ganglion spinal. On la rencontre dans le contexte de maladies autoimmunes, paranéoplasiques ou dégénératives. Il existe peu de littérature qui examine les caractéristiques électrophysiologiques du ganglion du trijumeau et les voies qui y sont associée ainsi que le réflexe de clignement (RC) chez les patients présentant une GS. Selon des études antérieures, le RC est conservé chez les cas de GS associée à une paranéoplasie. Méthode: Nous avons identifié dans la base de données de neurophysiologie clinique locale des patients ayant reçu un diagnostic de GS basé sur des études de conduction au niveau du nerf périphérique et chez qui le RC a été recherché. Vingt-six patients ont été inclus dans l'analyse finale. Résultats: Le syndrome de Sjögren était l'étiologie la plus fréquente de GS (8/26), suivi de cas idiopathiques (7/26) et de paranéoplasies (5/26). Des anomalies du RC ont été constatées chez 9 des 26 patients (34, 6%), toutes étiologies confondues. Aucun patient n'a rapporté de problèmes sensitifs dans le territoire du nerf trijumeau indiquant que les changements notés sont subcliniques. Trois patients présentaient une réponse R1 anormale. Chez les 6 autres patients, seulement les réponses R2 étaient touchées. Conclusions: Des anomalies subcliniques de R1 et R2 peuvent exister dans le contexte de GS d'étiologies variées, dont la paranéoplasie. Chez les patients chez qui on soupçonne une GS, le RC peut aider à fournir des indices additionnels d'une atteinte asymétrique des fibres sensitives, ce qui est caractéristique de la maladie.